Numerical optimization of a diesel combustion system to reduce soot mass and particle number density. (15th April 2020) - Duvvuri, Pavan Prakash; Shrivastava, Rajesh Kumar; Sreedhara, Sheshadri
Abstract: In view of the recent emission legislations imposing a limit on the soot particle number density, a numerical optimization has been presented for a constant speed heavy-duty diesel engine to reduce soot particle number density while ensuring no penalty on NOx emissions. Closed cycle combustion simulations have been performed at three loads with the sectional soot model coupled to gas phase kinetics. The combustion model has been tuned at each load to ensure a good agreement for in-cylinder pressure, heat release rate and exhaust emissions. The validated combustion model has been used to study the effect of various parameters like intake swirl, start of injection, number of nozzle holes, spray angle and piston bowl shapes. Combustion simulations have been performed for every case of a full factorial design of experiments with 486 cases. Change in plume dynamics due to each parameter has been discussed in detail with the help of in-cylinder soot contours. A reentrant bowl with a higher swirl, lower number of nozzle holes and a deeper spray angle has been found to be the most promising option as it reduces the exhaust soot mass, number density with no penalty on NOx and specific fuel consumption.